2016
DOI: 10.1016/j.watres.2016.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Strontium concentrations and isotope ratios in a forest-river system in the South Qinling Mts., China

Abstract: a b s t r a c tThe concentrations of dissolved strontium (Sr) and isotope ratios ( 87 Sr/ 86 Sr) in rainwater, river water, and water from forest soil are measured to investigate the contributions of these sources to a river during base flow conditions in the relatively pristine South Qinling Mountains, China. Dissolved Sr concentrations and 87 Sr/ 86 Sr ratios vary significantly between different water types (p < 0.01) suggesting that it is suitable for differentiating sources. Dissolved Sr is also positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…The measured values presumably reflected derivations in the Sr released during water-rock interactions that occurred in the subsurface of volcanic area, as low 87 Sr/ 86 Sr ratios were expected from the potassium volcanic rocks (0.70503 to 0.70589; Wang et al 1988). The 87 Sr/ 86 Sr ratios found in Quaternary potassium volcanic rocks in Wudalianchi, however, were much lower than the carbonate (∼0.71) and silicate (0.725) endmembers selected for the river system (Wang et al 2007;Bu et al 2016). Seasonally, the ratios were slightly lower in March and, to a lesser degree, in October, both of which were generally lower than in July, suggesting different mixing of endmembers across seasons (Figure 4(a)).…”
Section: Seasonal Variation Of 87 Sr/ 86 Srmentioning
confidence: 92%
See 1 more Smart Citation
“…The measured values presumably reflected derivations in the Sr released during water-rock interactions that occurred in the subsurface of volcanic area, as low 87 Sr/ 86 Sr ratios were expected from the potassium volcanic rocks (0.70503 to 0.70589; Wang et al 1988). The 87 Sr/ 86 Sr ratios found in Quaternary potassium volcanic rocks in Wudalianchi, however, were much lower than the carbonate (∼0.71) and silicate (0.725) endmembers selected for the river system (Wang et al 2007;Bu et al 2016). Seasonally, the ratios were slightly lower in March and, to a lesser degree, in October, both of which were generally lower than in July, suggesting different mixing of endmembers across seasons (Figure 4(a)).…”
Section: Seasonal Variation Of 87 Sr/ 86 Srmentioning
confidence: 92%
“…Hence, many case studies have highlighted the usefulness of the Sr isotope technique in hydrogeology to characterize the diversity of water-rock interactions and the mixing of water from different origins (Santoni et al 2016;Négrel et al 2018). The contributions of water from different sources often are determined by constructing binary mixing models of Sr ( 87 Sr/ 86 Sr) (Christensen et al 2018;Xue et al 2019) or by using multivariate mixing models based on mass balance equations of Sr concentration, 87 Sr/ 86 Sr ratios, δ 18 O, and other parameters (Phillips & Gregg 2001;Bu et al 2016;Santoni et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned above, both natural and anthropogenic sources contribute to the Sr budget of the Oder. Several previous studies have demonstrated that isotopic composition of Sr dissolved in streamwater, when coupled with Sr concentration data, allows identification of reservoirs that control the 87 Sr/ 86 Sr ratios and mixing processes involved (e.g., Bu et al, ; Jiang, ; Négrel, Petelet‐Giraud, & Widory, ; Zieliński et al, ). The 87 Sr/ 86 Sr ratios plotted versus 1/Sr in Figure for waters of the Oder River reveal a hydrological system with a very complex mixing relationships.…”
Section: Strontium Sources and Water Mixingmentioning
confidence: 99%
“…Strontium isotopes have also proved to be a reliable tool for identification of water reservoirs and aquifer interactions in a variety of hydrologic systems (e.g., Frost & Toner, ; Katz & Bullen, ; Négrel & Deschamps, ; Négrel & Pauwels, ; Zieliński et al, ). Among the various geochemical tracers commonly used to fingerprint fluid–rock reactions, strontium isotopes are particularly valuable in studies of weathering processes (e.g., Bu, Song, Zhang, & Burford, ; Jacobson, Blum, & Walter, ; Krishnaswami, Trivedi, Sarin, Ramesh, & Sharma, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation